Kanserli bireylerde ağrı ve ağrı ile başetme yöntemlerinin değerlendirilmesi - Afşar, Füsun (My University, 2002)
Amaç: Kanserli bireylerde ağrının değerlendirilmesi ve ağrıya yönelik başetme yöntemlerinin belirlenmesidir. Gereç ve Yöntem: Tanımlayıcı nitelikteki bu araştırma kanserli bireylerde ağrının değerlendirilmesi ve ağrıya yönelik başetme yöntemlerinin belirlenmesi amacıyla gerçekleştirilmiştir. Araştırmanın örneklemini, 1 Nisan - 1 Haziran 2001 tarihleri arasında İstanbul-Lütfü Kırdar Eğitim ve Araştırma Hastanesi'nde tedavi gören ve araştırmayı kabul eden 112 kanserli birey oluşturmuştur. Araştırma verileri bilgi formu ile ağrı tanılama ve başetme yöntemlerini değerlendirme formu kullanılarak elde edilmiştir. Verilerin yorumlanmasında; yüzdelik dağılımlar, ki-kare, t testi, varyans analizi ve pearson korelasyon testi kullanılmıştır. Bulgular: Olgularımızın %55.4'ü erkek ve %78.6'sının gelir düzeyi yetersiz olup; %31.3' ü akciğer kanseri, büyük çoğunluğu (%76) 0-1 yıldır kanserli ve %42.9' unun metastazı bulunmaktadır. Olguların ağrıları büyük oranda gövdede (%63.4) toplanmakta, %20.5'i ağrıyı yanıcı olarak nitelendirmekte, %67'sinin ağrısı stresle artmakta, %92'sinin analjezikle azalmakta ve en fazla fiziksel aktivitede azalma (%73.2) ağrıya eşlik etmektedir. Kabul edilebilir ağrı şiddeti (p<0.05) ve ağrının sözel ifadesinde (p<0.05) erkeklerin, duygusal ifadesinde (p<0.05) ise kadınların lehine olacak şekilde iki cins arasında fark bululmakta; kadınlarda bulantı-kusma (p<0.05) ve iştahsızlık (p<0.05) ağrıya daha fazla eşlik etmektedir. Ağrının en kötü (p<0.05) ve en az (p<0.01) zamandaki şiddeti ile sürekli ağrı (p<0.001) geliri giderini karşılayan grupta daha azdır ve bu grup ağrıyla başetmede dikkati başka yöne çekmeyi (p<0.05) daha fazla kullanmaktadır; geliri giderini karşılamayan bireylerde ise irritabilite (p<0.05) ve ağlama (p<0.05) ağrıya daha fazla eşlik etmektedir. Metastazı olanlarda ağrının şu andaki (p<0.01), en kötü (p<0.05) ve en az (p<0.01) zamandaki şiddeti daha fazladır ve sosyal aktivitede azalma (p<0.05) ağrıya daha fazla eşlik etmektedir. Ayaktan kemoterapi görenlerde oturma (p<0.05) ağrıyı beklenenden daha fazla arttırmakta; masaj (p<0.05), hareket (p<0.05) ve ortam değişikliği (p<0.001) beklenenden daha fazla azaltmaktadır. Hastanede yatan bireyler ağrıyla başetmede daha fazla analjezik kullanmakta (p<0.05), daha fazla yatıp/ dinlenmekte (p<0.05) ve bu grupta sosyal aktivitede azalma (p<0.01) ağrıya daha fazla eşlik etmektedir. Sonuç ve Öneriler: Etkili ağrı yönetiminde kanserli bireylerle çalışan sağlık ekibine rehber olacağı düşünüldüğünden, kanser ağrısının hemşireler tarafından düzenli olarak değerlendirilmesi önerilmektedir. Anahtar Sözcükler: kanser, ağrı, değerlendirme, başetme

The Evaluation of Pain and Methods of Coping with Pain in Cancer Patients Objective: Aim of this study was to evaluate pain in patients with cancer and to determine how such as pain could be managed. Method: This descriptive research is aimed at evaluating pain as suffered by patients with cancer and at determining how such pain could be managed. The survey was carried out in the Istanbul-Lütfü Kırdar Training hospital between the dates of 1'st April - 1'st June, 2001 and it covered a sample of 112 cases, who volunteered to participate. The data were obtained by means of two forms of General Information and Description and Coping Methods of Pain. Percentage distribution, chi-square, t test, variance analysis and Pearson's correlation test were made use of in interpreting the data. Results: 55.4% of our cases were males and 78.6% had a low income. 31.3% had lung cancer, 76% had cancer for a period of 0-1 yrs and 42.9% were suffering from the metastatic type of the cancer. Most of patients had pain in the trunk (63.4%), 20.5% described their suffering as a burning pain, the pain of 67% increased under stress, that of 92% decreased by taking analgesics, and in 73.2% a decrease in physical activity was the most common symptom which accompanied pain. It has been found out as a result of this survey that, having a reasonable level of pain (p<0.05), the male cases were in a better position compared to the female and were superior to them in verbal expressing their pain (p<0.05). However, the female group were at an advantage in emotionally expressing it (p<0.05). In female group pain was accompanied more by dizziness-vomiting (p<0.05) and loss of appetite (p<0.05). The worst pain (p<0.05) and the least pain (p<0.01) of those patients with a higher income than their expenses were better than other group. The constant pain of those patients with a higher income (p<0.001) was less than expected, and in coping with their pain, they were preferred the distraction method (p<0.05). It was determined that pain was accompanied more by crying (p<0.05) and irritability (p<0.05) than by other symptoms in patients with a lower income. The study has revealed that there was a relation between metastasis and the severity of the pain in its present pain (p<0.01), worst pain (p<0.05) and least pain (p<0.01). In this group, pain was accompanied more by a decrease in social activities (p<0.05) than by other symptoms. The outpatients receiving chemotherapy were noted to have a higher than expected level of pain in the sitting position (p<0.05), whereas massaging (p<0.05), making movements (p<0.05) and a change of environment (p<0.001) helped decrease pain more than expected. It was discovered that taking analgesics (p<0.05) and lying down/ resting (p<0.05) were preferred more by the inpatients, and that their pain was accompanied more by a decrease in social activities (p<0.01). Conclusion: It is hoped that this study will be of some use to the medical staff working to find an effective way of managing the pain of patients with cancer, and it is suggested that cancer pain be regularly evaluated by nurses. Key Words: cancer, pain, assessment, coping
Keywords: Hastalıklar; kan kanseri; Kanser; Kanserler; Sağlık; Teknoloji (Uygulamalı bilimler); Tıp bilimleri; Tümörler ve çeşitli bulaşıcı hastalıklar